A generalized Sard theorem on real closed fields. Issue 5 (18th January 2016) - Valette, Anna; Valette, Guillaume
Abstract : We work with semi‐algebraic functions on arbitrary real closed fields. We generalize the notion of critical values and prove a Sard type theorem in our framework.